Effect of fiber length and surface treatment on the performance of fiber-modified binder. (10th July 2020) - Xing, Xiangyang; Liu, Tao; Pei, Jianzhong; Huang, Jianyou; Li, Rui; Zhang, Jiupeng; Tian, Yefei
Highlights: Silane coupling agent improves the high temperature performance of aramid fiber modified asphalt. Silane coupling agent makes the surface of aramid fibers rough and hydrophobic. The increase of fiber length can improve the viscosity of fiber-modified asphalt binder. Abstract: In this study, the effects of fiber lengths and surface treatments of aramid fibers on the performance of aramid fiber-modified asphalt (AFMA) binders were examined. The surface treatment effects of aramid fibers with the silane coupling agent 3-methacryloxypropyltrimethoxysilane (KH-570) were investigated using scanning electron microscopy, a static contact angle method, and Fourier transform infrared spectroscopy. The length effects of the aramid fibers on the asphalt performance were studied using a dynamic shear rheometer, viscometer, and bending beam rheometer, and the improvement mechanisms were analyzed. The results show that an increase in fiber length can improve the viscosity of AFMA, and a reinforcement effect from short fibers with high content can be achieved by using long fibers with low content. It also indicated the silane coupling agent can enhance the bonding effect of fiber and asphalt. The results of this study can provide a reference for the application of fibers in asphalt binders and asphalt mixtures.